eHealth in Treatment of Offenders in Forensic Mental Health: A Review of the Current State - Kip, Hanneke; Bouman, Yvonne H. A.; Kelders, Saskia M.; van Gemert-Pijnen, Lisette J. E. W. C. (Frontiers in Psychiatry, 2018)
Background: Treatment of offenders in forensic mental health is complex. Often, these in- or outpatients have low treatment motivation, suffer from multiple disorders, and have poor literacy skills. eHealth may be able to improve treatment outcomes because of its potential to increase motivation and engagement, and it can overcome the predominant one-size-fits-all approach by being tailored to individual patients. Objective: In order to examine its potential, this systematic review studies the way that eHealth has been used and studied in forensic mental health and identifies accompanying advantages and disadvantages for both patients and treatment, including effectiveness. Methods: A systematic search in Scopus, PsycINFO and Web of Science was performed up until December 2017. Studies were included if they focused on technological interventions to improve the treatment of forensic psychiatric patients. Results: The search resulted in 50 studies in which eHealth was used for treatment purposes. Multiple types of studies and technologies were identified, such as virtual reality, web-based interventions and videoconferencing. The results confirmed the benefits of technology, for example the acquisition of unique information about offenders, effectiveness, and tailoring to specific characteristics, but indicated that these are not fully taken advantage of. Discussion: To overcome the barriers and obtain the benefits, eHealth has to have a good fit with patients and the forensic psychiatric context. It has to be seamlessly integrated in existing care and should not be added as an isolated element. In order to bridge the gap between the current situation and eHealth’s potential, further research on development, implementation and evaluation should be conducted.